The transformation of social work in Ukraine before and during the war - Romaniuk, Jaroslaw R.; Mamzer, Hanna; Farkas, Kathleen J. (Society Register, 2024)
Background: This article aims to review the development of the social work profession in Ukraine and to describe the impact of social, economic and political changes on social work practices and education. Methods: A comprehensive literature review and participant observation methods informed this study. A case study of a Polish community’s response to Ukrainian war refugees illustrates how social workers might capitalize on current social structures to continue strengthening civil society in Ukraine. Findings and Discussion: Social Work, focusing on the fit between person and environment, is shaped by knowledge, culture and belief systems. Ukraine’s history and transition from communist/centralized thinking to civil society is reflected in the development of social work to date. The impact of Russian invasions has hindered and strengthened how social workers can recognize and respond to needs. Limitations include the time lag between published articles and the rapidly changing situation in Ukraine. Originality/Value: Few articles focus on social work development in Ukraine, which adds to this article’s originality and relevance.